The reliability of in-hospital diagnoses of diabetes mellitus in the setting of an acute myocardial infarction - Arnold, Suzanne V (BMJ Open Diabetes Res Care, 2014)
OBJECTIVE: Incident diabetes mellitus (DM) is important to recognize in patients with acute myocardial infarction (AMI). To develop an efficient screening strategy, we explored the use of random plasma glucose (RPG) at admission and fasting plasma glucose (FPG) to select patients with AMI for glycosylated hemoglobin (HbA1c) testing. DESIGN, SETTING, ANDPARTICIPANTS: Prospective registry of 1574 patients with AMI not taking glucose-lowering medication from 24 US hospitals. All patients had HbA1c measured at a core laboratory and admission RPG and ≥2 FPGs recorded during hospitalization. We examined potential combinations of RPG and FPG and compared these with HbA1c≥6.5%—considered the gold standard for DM diagnosis in these analyses. RESULTS: An RPG>140 mg/dL or FPG≥126 mg/dL had high sensitivity for DM diagnosis. Combining these into a screening protocol (if admission RPG>140, check HbA1c; or if FPG≥126 on a subsequent day, check HbA1c) led to HbA1c testing in 50% of patients and identified 86% with incident DM (number needed to screen (NNS)=3.3 to identify 1 case of DM; vs NNS=5.6 with universal HbA1c screening). Alternatively, using an RPG>180 led to HbA1c testing in 40% of patients with AMI and identified 82% of DM (NNS=2.7). CONCLUSIONS: We have established two potential selective screening methods for DM in the setting of AMI that could identify the vast majority of incident DM by targeted screening of 40–50% of patients with AMI with HbA1c testing. Using these methods may efficiently identify patients with AMI with DM so that appropriate education and treatment can be promptly initiated.